A Rooted Horror: Thomas D'Arcy McGee and Secret Societies, 1845-68 - A. Wilson, David (The Canadian Journal of Irish Studies, 2005)
Keywords: Féniens; Irlandais; McGee, Thomas D'Arcy; Nationalisme

Widows Negotiate the Law: The First Year of Widowhood in Early-Nineteenth-Century Montreal - Bradbury, Bettina (Negotiating Identities in 19th- and 20th- Century Montreal, 2005)
Keywords: Femmes; Veuvage

BENOIT, ZÉPHIRIN - Charbonneau, Hélène (Dictionnaire biographique du Canada, 2005)

CREIGHTON, JAMES GEORGE AYLWIN - Fitsell, J.W. (Dictionnaire biographique du Canada, 2005)

WILSON, ERASTUS WILLIAM - Gagnon, Jean-Pierre (Dictionnaire biographique du Canada, 2005)

RODDICK, sir THOMAS GEORGE - Hanaway, Joseph (Dictionnaire biographique du Canada, 2005)

Le printemps de l'Amérique française: américanité, anticolonialisme et républicanisme dans le discours politique québécois, 1805-1837 - Harvey, Louis-Georges (Boréal, 2005)
Keywords: Idéologies

The Radicalization of the Montreal Irish: The Role of the "Vindicator" - Jackson, James (The Canadian Journal of Irish Studies, 2005)
Keywords: Irlandais; Rébellions; The Vindicator

GADBOIS, JOSEPH-PIERRE - Janson, Gilles (Dictionnaire biographique du Canada, 2005)

BICKERDIKE, ROBERT - Jedwab, Jack (Dictionnaire biographique du Canada, 2005)

GOUIN, sir LOMER - Jones, Richard (Dictionnaire biographique du Canada, 2005)

La milice du district de Montréal, 1787-1829: essai d'histoire socio-militaire - Lépine, Luc (Université du Québec à Montréal, 2005)
Keywords: Milice

VERVILLE, ALPHONSE - Leroux, Éric (Dictionnaire biographique du Canada, 2005)

MEREDITH, sir HENRY VINCENT - McDowall, Duncan (Dictionnaire biographique du Canada, 2005)

McCORD, DAVID ROSS - Miller, Pamela (Dictionnaire biographique du Canada, 2005)

French Canadians and the Beginning of the War of 1812: Revisiting the Lachine Riot - Mills, Sean (Histoire sociale / Social History, 2005)
Historians have generally claimed that, during the War of 1812, unlike in earlier periods, French Canadians eagerly rallied to the British cause and willingly fought to defend British North America from American invasion. Nearly all studies of French-Canadian participation in the war, however, focus on the Battle of Châteauguay in 1813, and few examine the first year of the war. A close look at French Canadians’ reactions to the outbreak of the War of 1812 would indicate that they were hardly unanimous in their support. A detailed study of the largest and most violent act of resistance — a riot that broke out at Lachine at the beginning of July 1812 — reveals some of the reasons why so many habitants refused to perform their militia duty.
Keywords: Guerre; Lachine; Émeutes

TAILLON, sir LOUIS-OLIVIER - Munro, Kenneth (Dictionnaire biographique du Canada, 2005)

CHOQUET, FRANÇOIS-XAVIER - Myers, Tamara (Dictionnaire biographique du Canada, 2005)

« What a Misfortune that Poor Child Should Have Married Such a Being as Joe »: Les fils prodigues de la bourgeoisie montréalaise, 1850-1900 - Nootens, Thierry (Canadian Historical Review, 2005)
Keywords: Bourgeoisie

BEAUCHAMP, JEAN-JOSEPH - Normand, Sylvio (Dictionnaire biographique du Canada, 2005)

LACOSTE, sir ALEXANDRE - Normand, sylvio (Dictionnaire biographique du Canada, 2005)

Augustin-Norbert Morin, 1803-1865 - Paradis, Jean-Marc (Septentrion, 2005)
Keywords: Avocats; Rébellions

GOHIER, ÉDOUARD - Poitras, Claire (Dictionnaire biographique du Canada, 2005)

DUCHARME, GUILLAUME-NARCISSE - Saint-Pierre, Jacques (Dictionnaire biographique du Canada, 2005)

VALLÉE, CHARLES-AMÉDÉE - Tremblay, Marie J. (Dictionnaire biographique du Canada, 2005)

FABIEN, CLÉOPHAS - Tremblay, Robert (Dictionnaire biographique du Canada, 2005)

KEMP, sir ALBERT EDWARD - Turley-Ewart, John A.; Brown, Craig (Dictionnaire biographique du Canada, 2005)

PELLETIER, ROMAIN-OCTAVE - Vachon, Pierre (Dictionnaire biographique du Canada, 2005)